Comparison of reliability, validity, and accuracy of linear measurements made on pre- and posttreatment digital study models with conventional plaster study models - Raj Kumar Verma; Satinder Pal Singh; Sanjeev Verma; Vinay Kumar; Nameksh Raj Bhupali; Sohail Arora (Wolters Kluwer Medknow Publications, 2019)
OBJECTIVES: To compare the accuracy of the linear measurements made on pre- and posttreatment three-dimensional (3D) scanned digital models with conventional plaster study models. MATERIALS AND METHODS: The study was conducted on pre- and posttreatment study models of 132 patients. A 3D model scanner was used to scan the plaster models to form 3D digital models. The measurements were made on the plaster models using digital Vernier calipers, and the 3D digital models were assessed for similar measurement using a software of the model scanner. The intraclass correlation for intraoperator error showed good correlations between the measurements made on conventional plaster models and digital models. RESULTS: Although the comparison of the linear measurements made by conventional and digital methods on both pre- and posttreatment study models using intraclass coefficient showed a good correlation, analysis of variance showed significant mean differences in the measurements of multiple variables in both the groups. The number of variables showing significant differences was more in the pretreatment group. The measurements obtained by Vernier calipers were generally higher than those of scanned pre- and posttreatment study models. CONCLUSION: The linear measurements made by conventional and digital methods showed statistically significant mean differences. The accuracy of recording can be affected by the severity of pretreatment malocclusion, but the deviations were not large enough to contradict the use of the digital models for orthodontic records.